Azetidine iminosugars from the cyclization of 3,5-di-O-triflates of α-furanosides and of 2,4-di-O-triflates of β-pyranosides derived from glucose. - Lenagh-Snow, G; Araújo, N; Jenkinson, S; Martínez, R; Shimada, Y; Yu, C; Kato, A; Fleet, G (2012)
Primary amines with either 3,5-di-O-ditriflates of α-furanosides or 2,4-di-O-triflates of β-pyranosides form bicyclic azetidines in high yield.